Prevalence of Obesity in mid adolescents in central India: a school based study - Sharma, Roop; Mandliya, Jagdish; Dhaneria, Mamta; Tiwari, H.L (International Journal of Medical Research and Review, 2015)
Introduction: Overweight and obesity among children and adolescents has increased significantly in the developed countries during the past two decades and similar trends are being observed even in the developing world. Methods: Mid adolescent boys and girls (14-16years) of three government and four private schools of Ujjain city were included with sample size of 1000. A pre designed questionnaire regarding nutritional and dietary history was prepared with measurement of anthropometry. Results: The overall prevalence of overweight and obese children in the present study was 6.8% and 3.7% respectively. The combined prevalence of overweight and obesity in the private and government schools was 12.2% and 8.4% respectively (p<0.05). Excess calorie intake was seen with 92.3 % of obese children in government compared to 50.8% in private school (p=0.00). It was also found in our study that less outdoor activity, and spending more time with computer and TV was more common in overweight and obese children. Conclusion The combined prevalence of overweight and obesity was much higher in private schools than government school. BMI underestimates the obesity while WHR is the better indicator for early detection of central obesity in the adolescent age group. Various factors which were found to have correlation with overweight and obesity included calorie intake, number of meals per day, lack of physical activity and overindulgence in indoor activity in the present study.